A review on potential of biohydrogen generation through waste decomposition technologies - Chai, Y.H. (Springer Science and Business Media Deutschland GmbH, 2021)
This article reviews various waste decomposition technologies composed of thermochemical and biochemical conversion routes for the generation of biohydrogen from biomass wastes. Due to the escalation of global energy consumptions, concerns on the energy security fuelled increasing generation of energy processes to meet such demands. The development of hydrogen has always sustained interest due to its immense prospects as a clean energy source. Instead, the current hydrogen production process termed as grey hydrogen posed the main contributing factor for carbon-related emissions. Therefore, technological prospects for green hydrogen (biohydrogen) production in the transition towards a decarbonised energy sector are desirable and advantageous. Furthermore, current constraints associated to the production of biohydrogen, ranging from safety to transportation aspects, are also discussed to provide informative insights to researchers and decision makers for a better understanding of biohydrogen economy. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.